REMOTE STUDENT TRAINING OF STUDENTS OF THE EARLY DIVISION - Olga M. Sevostyanova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Mixed technique involves the integration of classical full-time and distance learning and contributes to the quality of the educational process. A certain proportion of graphic disciplines the students learn in full-time education, and the other - with the use of synchronous and asynchronous distance learning. The simplest and most economical way of synchronous learning is Skype. For transmission of graphics (complex drawings) is applied IDroo (virtual whiteboard). IDroo plugin must be installed on the computers of the tutor and the student, which makes it possible to collaboratively edit the graphic solution of problems of descriptive geometry in-line mode. Virtual board has a simple interface and easy to learn students. The article discusses the technique of application IDroo plugin.When conducting asynchronous learning using case studies, which include multimedia lectures, assignments for independent decisions, guidelines for solving problems with animated fragments, assessment criteria, test for self-control, schedule control activities and schedule remote consultations. Depending on the level of training and personal characteristics of the student chooses their own path of study of educational material, tempo, volume, etc.The article provides an analysis of the full-time and distance learning, indicating their advantages and disadvantages. The greatest effect can be achieved by the integration of full-time, asynchronous and synchronous learning. Such training is called mixed (Blended learning). The use of blended learning for full-time students contribute to the motivation of cognitive activity, the development of skills of independent work creates awareness, self-discipline, develops creativity. The article describes the method of classroom and remote consultations using mixed technology.